The Ecosystem Services Benchmark - Hill, Margot; Mulder, Ivo; Grigg, Annelisa; Cullen, Zoe; Foxall, Jack (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
The impacts and dependences of companies on natural resources is a key factor for their future performance. The new Ecosystem Services Benchmark identifies risks and performances of companies and provides a strategic framework on the issue, often overlooked in established management systems.
Keywords: Benchmark System; Biodiversität